Oscillometry for personalizing continuous distending pressure maneuvers: an observational study in extremely preterm infants - Chiara Veneroni; Raffaele L. Dellacà; Erik Küng; Beatrice Bonomi; Angelika Berger; Tobias Werther (Respiratory Research, 2024)
Abstract Rationale Lung recruitment and continuous distending pressure (CDP) titration are critical for assuring the efficacy of high-frequency ventilation (HFOV) in preterm infants. The limitation of oxygenation (peripheral oxygen saturation, SpO2) in optimizing CDP calls for evaluating other non-invasive bedside measurements. Respiratory reactance (Xrs) at 10 Hz measured by oscillometry reflects lung volume recruitment and tissue strain. In particular, lung volume recruitment and decreased tissue strain result in increased Xrs values. Objectives In extremely preterm infants treated with HFOV as first intention, we aimed to measure the relationship between CDP and Xrs during SpO2-driven CDP optimization. Methods In this prospective observational study, extremely preterm infants born before 28 weeks of gestation undergoing SpO2-guided lung recruitment maneuvers were included in the study. SpO2 and Xrs were recorded at each CDP step. The optimal CDP identified by oxygenation (CDPOpt_SpO2) was compared to the CDP providing maximal Xrs on the deflation limb of the recruitment maneuver (CDPXrs). Results We studied 40 infants (gestational age at birth = 22+ 6-27+ 5 wk; postnatal age = 1–23 days). Measurements were well tolerated and provided reliable results in 96% of cases. On average, Xrs decreased during the inflation limb and increased during the deflation limb. Xrs changes were heterogeneous among the infants for the amount of decrease with increasing CDP, the decrease at the lowest CDP of the deflation limb, and the hysteresis of the Xrs vs. CDP curve. In all but five infants, the hysteresis of the Xrs vs. CDP curve suggested effective lung recruitment. CDPOpt_SpO2 and CDPXrs were highly correlated (ρ = 0.71, p < 0.001) and not statistically different (median difference [range] = -1 [-3; 9] cmH2O). However, CDPXrs were equal to CDPOpt_SpO2 in only 6 infants, greater than CDPOpt_SpO2 in 10, and lower in 24 infants. Conclusions The Xrs changes described provide complementary information to oxygenation. Further investigation is warranted to refine recruitment maneuvers and CPD settings in preterm infants.